2013
DOI: 10.1159/000348832
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Diagnosis and Management of Neuroendocrine Tumors: Utilizing New Advances in Biomarker and Molecular Imaging Science

Abstract: Neuroendocrine tumors (NET) are malignant solid tumors that arise in hormone-secreting tissue of the diffuse neuroendocrine system or endocrine glands. Although traditionally understood to be a rare disease, the incidence and prevalence of NET have increased greatly in the past 3 decades. However, during this time, progress in diagnosis and outcome of NET has generally been modest. In order to achieve improved outcome in NET, a better understanding of NET biology combined with more reliable serum markers and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Monoanalytes, such as CgA, have been used in conjunction with clinical information to aid the interpretation of imaging with varying degrees of clinical efficacy [19,15]. Many NET patients (~30-50 %) do not have elevated CgA [43], and CgA exhibits low specific metrics with a wide variation in values depending upon the assay type, the laboratory, and numerous coexisting factors (renal insufficiency, proton pump inhibitors) [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoanalytes, such as CgA, have been used in conjunction with clinical information to aid the interpretation of imaging with varying degrees of clinical efficacy [19,15]. Many NET patients (~30-50 %) do not have elevated CgA [43], and CgA exhibits low specific metrics with a wide variation in values depending upon the assay type, the laboratory, and numerous coexisting factors (renal insufficiency, proton pump inhibitors) [12].…”
Section: Discussionmentioning
confidence: 99%
“…An amalgamation of biomarker and imaging technologies may provide an opportunity to optimize accurate detection and early determination of disease progress [19,4]. We hypothesized that imaging and biomarkers may capture similar biological information and that combinations of this information could be of clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…An informative source of information would be the integration of tumor data, such as circulating tumor cells and relevant genes, detected through mRNA measurement or circulating autoantibodies, with imaging [113]. In particular, circulating genomic data obtained from blood (tumor transcript profile or signature) at the time of imaging could be combined with morphologic or functional tumor characteristics and, thus, allow for the development of a personalized predictive assessment of tumor status before, during and after treatment [3].…”
Section: Integration Of Biological Information To Amplify Accuracymentioning
confidence: 99%
“…However, a recent forum of global leaders in the field of NETs concluded that an unmet need exists for additional therapies [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Short- and long-term hematological toxicity after 4 cycles of 7.8 GBq 177 Lu-DOTA-octreotate PRRT with concomitant capecitabine and temozolomide chemotherapy in our GEP NET patients was characterized and compared with published data for PRRT with 177 Lu-DOTA-octreotate [4,5,10] and 90 Y-DOTATOC [1,2], used alone or in combination [7]. The hematological toxicity of nonradioactive therapy of pancreatic NETs with somatostatin analogs [11] and the recently approved biological agents everolimus [12,13] and sunitinib [14] are also reviewed.…”
Section: Introductionmentioning
confidence: 99%